Exploring How One’s Primary Financial Conversant Varies by Marital Status - Megan McCoy; Kenneth J White; XianYan Chen (Journal of Financial Therapy, 2019)
Research has shown communication around finances is essential to relational satisfaction, yet often couples avoid these money talks. In this study, we examined how the financial discussions were impacted by marital status. The findings were surprising. Married people were the least likely to be engaging in money talks with their partner, all of the other participants (e.g., cohabitating, dating, separated) were all engaging their partners at much greater rates in money talks. However, married respondents were talking to their family members, friends, financial professionals, and other professionals about money. These different conversations were analyzed through the lens of social capital to explore how different couple typologies may impact their tendencies to use bridging or bonding social capital. Finally, the results suggest that other aspects of human capital (e.g., health, education, age) also related to rates of financial conversations. The findings of this study have strong implications for financial professionals, financial therapists, mental health professionals, as well as, implications for anyone in a romantic relationship.
Keywords: financial conversations; social capital; bonding; bridging; relational satisfaction; financial therapy